2018
DOI: 10.1080/10758216.2018.1474716
|View full text |Cite
|
Sign up to set email alerts
|

Back to Normalization or Conflict with China in Greater Central Asia?

Abstract: Over the past few decades, China has been engaged in development projects and soft power initiatives in many regions of the world. In some cases, the perceptions are distinctly positive. The negative perceptions are at times accompanied by protests and other forms of dissent. Several quantitative and qualitative studies have been done in this regard in Greater Central Asia (GCA), but comparisons across GCA countries are rare. This paper fills the void. Survey analysis, desktop research of materials of various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The reason is that most of the agreements are not actually yet realized as projects. More and more studies have also shown that the BRI tends to be only known, articulated, or even supported by specific elites in certain countries (e.g., Chen and Günther 2018;Bitabarova 2018;Liu and Lim 2018;Matura 2018;Chen and Jiménez-Tovar 2017). Political and/or business elites in recipient states are more likely to see the benefits that the BRI can bring to themselves, their communities, and societies, and thus start to mobilize and form networks to make the BRI a reality in their countries.…”
Section: A Critical Discussion Of China-centric Approachesmentioning
confidence: 99%
“…The reason is that most of the agreements are not actually yet realized as projects. More and more studies have also shown that the BRI tends to be only known, articulated, or even supported by specific elites in certain countries (e.g., Chen and Günther 2018;Bitabarova 2018;Liu and Lim 2018;Matura 2018;Chen and Jiménez-Tovar 2017). Political and/or business elites in recipient states are more likely to see the benefits that the BRI can bring to themselves, their communities, and societies, and thus start to mobilize and form networks to make the BRI a reality in their countries.…”
Section: A Critical Discussion Of China-centric Approachesmentioning
confidence: 99%
“…Together these different cultural mediums create powerful geopolitical discourses which reflect, shape and subvert the prevailing political anxieties of their time. Critical geopolitics theorist Simon Dalby (1991: 274) writes that ‘the essential moment of geopolitical discourse is the division of space into “our” place and “their” place; its political function being to incorporate and regulate “us” or “the same” by distinguishing “us” from “them”, “the same” from “the other”’. In recognizing the importance of popular culture / mass media and examining their influence on perceptions of China in Kyrgyzstan, we included several questions to explore which cultural products were influential in shaping students’ worldviews (such as the question on watching TV shows or movies from countries other than one's own).…”
Section: Methodsmentioning
confidence: 99%
“…Chen and Jiménez-Tovar (2017) and Chen and Günther (2020) are among the few examples of survey work on Central Asian perceptions of China. Like us, their surveys are limited to the views of students due to their relative ease of access for academics.…”
Section: Central Asian Contextmentioning
confidence: 99%
“…This implies that an international image of a state is never monolithic, but rather is a complex entity consisting of various internal components. It is analytically unfeasible to identify and examine every single component of the image, thus the main question for an analyst is to identify which components or dimensions of the image to focus on (Cottam, 1977: 43; Herrmann, 1985: 26). Image theorists also suggest that in this plethora of internal dimensions of the international image, the three most important dimensions are: (1) a perception of an object’s relative power, (2) a perception of whether an object represents an opportunity or poses a threat to one’s own country, and (3) a perception of cultural proximity between one’s own country and a perceived country (Herrmann, 2013; Herrmann et al, 1997).…”
Section: Conceptual and Methodological Approachmentioning
confidence: 99%
“…Radio Azattyq, 2019). Given the growing importance of the issue of Sinophobia in Central Asia, this topic has come under close scholarly scrutiny (Burkhanov and Chen, 2016;Chen and Günther, 2020;Clarke, 2014;Laruelle and Peyrouse, 2012;Owen, 2018;Shailoobek Kyzy, 2021;Syroezhkin, 2014;Toktomushev, 2021).…”
Section: Introductionmentioning
confidence: 99%